La “Atenas suramericana”. Búsqueda de los orígenes de la denominación dada a Bogotá - Montenegro González, Augusto (Pontificia Universidad Javeriana, 2014)
The author analyzes the work and books of travelers, diplomats and literary figures from the 19th century in which the title "Athens" is attributed to Bogota. The author explains the origins and diffusion of this qualifying term as it applies to Bogota since the actual origins of the term have been hidden under a veneer if "custom" and everyday usage.